A Comparison of Clinical Examination and Magnetic Resonance Imaging Results with Arthroscopy Results in Knee Intra-Articular Pathologies - Mehmet Sabri Balık; Rıfat Şahin (Sakarya Tıp Dergisi)
Objective: We aimed to determine in which of the symptomatic intra-articular pathologies of the knee, clinical examination and magnetic resonance imaging (MRI) can be an alternative to diagnostic arthroscopy. Materials and Methods: Prospective analysis of 50 patients aged 18 to 50 years who underwent arthroscopy with the diagnosis of meniscus tear, cruciate ligament injury, cartilage damage, or plica between 2013 and 2015 was conducted. The results of the physical examination and MRI were compared with arthroscopy findings. Results: Patients with a mean age of 35 years. Sensitivity, specificity, and accuracy rates in the Mc-Murray test were 90%, 11%, 76%; 76%, 33%, 68% in the Apley test; and 80%, 33%, 72% in the Ege’s test. Sensitivity, specificity, and accuracy rates in the MRI for the medial meniscus were 87%, 68%, 80%; 92%, 92%, 92% for the lateral meniscus; 36%, 95%, 62% for chondral injury; 90%, 95%, 94% for the anterior cruciate ligament; and 21%, 59%, 34% in the plica. Conclusion: It should be noted that positive results can also be obtained in other knee intra-articular pathologies other than meniscus tear, as the sensitivity of these tests used to diagnose meniscus tear is high, but specificity is low. 1.5-tesla MRI has a high accuracy rate for detecting meniscus and anterior cruciate ligament injuries, while the diagnostic power of chondral surface evaluation remains limited, and high-resolution cartilagespecific images are required. As it is insufficient for evaluating plica on its own, it must be carefully incorporated during arthroscopy.